EPIDEMIOLOGY OF LIVER CANCER. MORBIDITY, MORTALITY, DYNAMICS OF HISTOLOGICAL STRUCTURE - V. M. Merabishvili; E. N. Merabishvili; O. F. Chepik (Сибирский онкологический журнал, 2016)
Primary liver cancer is the ICD-10 category C22 (malignant tumors of the liver and intrahepatic bile ducts). This is one of the most severe forms of cancer. According to database (DB) of the Population-based Cancer Registry of St. Petersburg for the past 15 years the median of cumulative observed survival of liver cancer patients of all histological forms (excluding postmortem diagnosed patients) both for men and women was no more than 3.3 months from the moment of diagnosis. On the majority of administrative territories of Russia mortality from liver cancer exceeds the level of morbidity that indicates a significant underestimation of primary patients. Even mortality («rude» rate) for Russia in the whole for men in 2012 exceeded the level of morbidity. St. Petersburg (Leningrad) is the single territory of Russia where the dynamics of the population liver cancer incidence can be analyzed since 1980. Dynamics of histological structure of liver cancer, recorded in St. Petersburg, shows a sharp decline in the proportion of tumors of the liver without a specific histological type and the significant increase in hepatocellular carcinoma and cholangiocarcinoma. Purpose of the study. To study the prevalence of liver cancer in the world and Russia, to produce in-depth development of material based on DB of the Population-based Cancer Registry of St. Petersburg. Material and methods. For the study there were taken by international data of the program «Cancer in 5 continents», statistical materials on Russia, 3893 cases from DB of the Population-based Cancer Registry of St. Petersburg, estimated analytical indices, index accuracy. Results of the study. Liver cancer is the most severe form of cancer. It is practically not detected in stage I and II of disease, index of accuracy in the most administrative territories exceeds 1.0. Conclusion. Thus liver cancer is not only one of tumors with the highest lethality and the lowest median of survival but also has a significant underestimation of the primary cases. Since the introduction in public reporting data on deaths from liver cancer in 1999 the standardized mortality rate in St. Petersburg decreased by 17.2 % in men and 16.0 % women.